COMPARATIVE STUDY OF SPEED BREEDING EFFICIENCY IN PEANUT CULTIVARS UNDER DIFFERENT SOIL MIXTURES - Maria Zahid; Muhammad Hassan Asadi; Mahmood ul Hassan; Ghulam Shabbir; Muhammad Sheeraz Ahmad (Policy Research Journal, 2025)
Climate change threatens crop sustainability. Rapid Generation Advance, like speed breeding, can reduce growth time and improve peanut production in Pakistan. However, legal implications remain. The study investigated the effectiveness of speed breeding in advancing three peanut cultivars under different potting media ratios. The study recorded three generations of each cultivar, subjected them to dormancy breakage, and analyzed their morphological characteristics. The experiment revealed significant differences in morphological parameters among genotypes and treatments, with BARI-2011 showing the highest number of branches, earliest flowering, and peg emergence. The ratio of sand, silt, and manure (60:30:10) provided the most acceptable results in peg emergence and flower initiation. It has been observed from the results that the interaction between the ratio of sand, silt and manure (30:60:10) and BARI-2011 was more dominant in having more primary and secondary branches, days to germination, plant height, and early flower initiation, and peg emergence in almost every generation. However, the current study is not particularly based on genetic variations of the varieties but entirely on environmental variations. Therefore, it is concluded that this genotype can be used by plant breeders to get 3 to 4 generations of peanuts in one year under the facilities of speed breeding.